(3CfXeI GdeYdheGJ GdLZQGajIs - (3bGSe(B, (3GdOhjcGfs ((3YeGf(B:s ((3O(B.(3J(B),s, 2000)
(3JYQja CfXeI GdeYdheGJ GdLZQGajI hYfGUQgG hHQeLjGJgG,YfGUQ hGSJNOGeGJ CfXeI GdeYdheGJ GdLZQGajI,HQeLjGJ CfXeI GdeYdheGJ GdLZQGajI,GdCLgRI GdUdHI(B/(3GdcjGf GdeGOj aj CfXeI GdeYdheGJ GdLZQGajI,fXe GdJTZjd hHQeLjGJ CfXeI GdeYdheGJ GdLZQGajI,bGYOI GdHjGfGJ aj CfXeI GdeYdheGJ GdLZQGajI,GONGd GdHjGfGJ GdecGfjI hGdJMbb efgG hJUMjMgG hJNRjfgG,eQGLYI GdeYdheGJ GdecGfjI hJUMjMgG,CSGdjH GdJMdjd GdLZQGaj hGdhUaj aj CfXeI GdeYdheGJ GdLZQGajI,HfGA fXGe eYdheGJj LZQGaj,HQeLjGJ GQfcah dHfGA CfXeI GdeYdheGJ GdLZQGajIs
Keywords: (3GdLZQGajGs; (3GdLZQGajG(B-(3fXe GdeYdheGJ s